The Use of Venom and Venom-Derived Products in Medicine and Cosmetics: the Ethical Issues From Islamic Perspective - Ahmad Rusmil, Muhamad Rusdi; Othman, Iekhsan; Che Mohamad, Che Anuar (IIUM Medical Journal Malaysia, 2018)
Venom is a mixture of biologically active toxins that affect normal physiological functions. With the advance in technology, the complexity and functions of venom and its toxins are slowly being revealed. It has become important source for therapeutic, diagnostic and cosmetic agents. However, there is concern among the Muslim community pertaining to halal and safety issues on the venom and venom-derived product usage. There are few studies that discuss the Islamic views in the usage of venom and venom-based product in medicine and cosmetic applications. There is a need for Muslim scientists and scholars to seriously identify the potential ethical and safety issues in the usage of venom and venom-derived products in view of the widespread application in medicine and cosmetic, which subsequently forming the basis for relevant and reliable shariah ruling. This is an attempt to review the relevant articles based on the following keywords: venom and Islamic ruling, venom-based product, venom and medicine, venom and cosmetic, antivenom, venom toxin, snake poison and venom diagnostics. It will also attempt to clarify and elaborate the implication of the “halal” status for venom-based product. Finaly the current available shariah rulings on the usage of venom and venom-based product both in medical and cosmetic area and the related principle of fiqh involved will be analyzed. The findings from this review, particularly the current available ruling will allow various parties to be well informed on the current ruling and related issues on the usage of this products.